The Implementation of Community Empowerment Program in Reducing the Poverty (Case Study of PNPM-Mandiri Urban in Besito Village, Gebog Sub-district, Kudus Regency, Central Java Province, Indonesia) - Noor Chayati; Sarwono Sarwono; Mardiyono Mardiyono (Wacana Journal of Social and Humanity Studies, 2013)
PNPM-Mandiri as community empowerment program is a national program to accelerate the poverty reduction. The implementation of the program in some areas showed the successful by the poverty reduction. Nevertheless, many areas failed in implementing the program showed by the poverty remains, even worse. Therefore, it needs further analysis whether successful of the implementation of the program could not automatically reduce the poverty rate. The problem was occured in Besito Village Gebog Sub-District Kudus Regency. BKM Besito Makmur, the community based organization in the Village, won Kudus Regency awards in some years and also from Provincial level, but the poverty rate is still relatively high. This research used qualitative method in analyzing the implementation of PNPM Mandiri Urban in Besito Village, a community empowerment project supported by World Bank joint funded by local community. Besides this research analyzed the effectiveness of PNPM - Mandiri in reducing the poverty, this research also analyzed the roles of stakeholders to reduce the poverty through PNPM - Mandiri, the constraining factors, and the result of program implementation. As a result of evaluation, this program seems to be failed in terms of poverty reduction as final goal. The poverty reduction in Besito Village cannot be achieved although the BKM won awards because the implementation of the program only good in administration. The roles of stakeholders were not optimal, since the poor, women, and community leaders were not involved in all activities especially in the planning stage. The constraining factors divided into two categories, structural problems and operational problems. The poverty alleviation program needs some improvement to be more effective, efficient, relevant, sustainable and give positive impact in reducing the poverty. To cope with, the poor should be centered in implementing the program. Keywords: Community Empowerment; Poverty Reduction; National Program